Reluctance in Clinicians to Start Clozapine Treatment: A Heavy Toll in Clinical Outcome in Schizophrenia - Ghulam Hassan, Muhammad Ali Awab Sarwar, Benazir Javed, Umair Mudassar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Purpose of our study is to determine the frequency of treatment with clozapine among patients with treatment resistance schizophrenia. Study Design: Cross sectional study Place and Duration: Sughra Shafi Medical Complex Narowal. April 2020-October 2020 Methods: Total 23 patients of both genders had age 25-50 years were presented. All the patients had treatment-resistance schizophrenia and admitted to hospital for treatment.Only 4 patients were on clozapine while 19 patients were on other Antipsychotics. Patients were enrolled after taking informed written consent for detailed demographics. SPSS 22.0 was used to analyze all data. Results:Among 23 patients, 17 (73.9%) were males and 6 (26.1%) cases were females.Mean age of the the patients was 34.16±8.30 years and had mean BMI 24.2±6.37 kg/m2. Majority patients 15 (65.2%) had poor socio-economic status and 13 (56.5%) cases had urban residency. Only 4 (17.4%) patients received clozapine treatment. Psychiatristswere hesitating to provide clozapine among 19 (82.6%) cases. Reasons for hesitance to prescribe clozapine included concerns about major adverse effects and patients’ lack of adherence, as well as difficulties in finding appropriate patients, service fragmentation, and a lack of familiarity with the drug. Conclusion:Clozapine continues to be under prescribed for individuals with treatment-resistant schizophrenia owing to several hurdles relating to the physician, the system of care, and technology. In order to overcome these obstacles, it is suggested that prescriber expertise and training be enhanced, integrated care be implemented, and technology be used to provide continuous, real-time monitoring of blood tests. Keywords:Treatment-resistance Schizophrenia, Clozapine, Complications, Antipsychotics